Investigating perspective taking and caregiver-proxy–child communication attitude agreement in early childhood stuttering - Katie L. Winters; Courtney T. Byrd (PLoS ONE, 2026)
Purpose Children begin to stutter and develop early attitudes about their communication during a critical period of speech, language, and social cognition development. This study examined social cognition via cognitive and affective perspective taking and explored whether perspective taking influences caregiver-proxy – child communication attitude agreement in 3–6-year-old children who stutter, while accounting for variation in speech and language abilities. Method One hundred eleven children who stutter, ages 3–6, completed the KiddyCAT, protocols for cognitive and affective perspective taking, and standardized speech and language assessments. One primary caregiver completed an adapted version of the KiddyCAT , which involved estimating their perception of their child’s communication attitude. Analyses were conducted to calculate the caregiver’s item-by-item agreement with their child’s responses on the KiddyCAT , and multiple regression was used to assess predictors of caregiver-proxy – child KiddyCAT agreement. Results Approximately 8% of children performed above chance on the cognitive perspective taking task, whereas 56% performed above chance on the affective task. Caregiver-proxy – child KiddyCAT agreement ranged from 0.56–0.85, with higher agreement on two items requiring the child’s perspective taking. Higher speech and language scores predicted greater KiddyCAT agreement for all caregiver-child dyads. Neither affective nor cognitive perspective taking predicted KiddyCAT agreement. Conclusions Consistent with research with typically developing children, there is substantial variability in perspective taking in children age 3–6 who stutter, with evidence of emerging affective, but comparatively limited cognitive perspective taking skills. Caregiver-proxy – child agreement on the Kiddy-CAT, a measure that requires both affective and cognitive perspective taking, appears to be stronger for children with more advanced speech and language. Given that at least some young children and their caregivers appear to be aware of each other’s perspectives regarding the child’s communication, clinicians should facilitate discussion of stuttering and reactions to stuttering openly and neutrally with these caregivers and their children.